AB0094 Monocytes expressing fc gamma receptor 3b (cd16b) is significantly increased in patients with active rheumatoid arthritis. (23rd January 2014) - Tsukamoto, M.; Yoshimoto, K.; Kameda, H.; Takeuchi, T.
Abstract : Background: We have previously demonstrated that high affinity polymorphism of Fc gamma receptor 3b (NA1/NA1), but not Fc gamma receptor 3a, is associated with infusion reaction to IgG1 monoclonal antibodies, such as infliximab and adalimumab, in patients with active rheumatoid arthritis (RA). While the expression of Fc gamma receptor 3b (CD16b) has been reported to be on neutrophils, mast cells and basophils in normal individuals, it has not been fully elucidated in patients with RA. Objectives: To examine the expression of CD16 or CD16b on CD14+ monocytes, CD14-CD3- cells, or CD203c+ cells in RA patients in comparison with healthy controls, and a possible correlation between the number of CD16b or CD16 positive cells and RA disease activity. Methods: Consecutive patients with RA who fulfilled the 1987 revised criteria of the American College of Rheumatology (ACR) for the classification of RA or the 2010 ACR/EULAR RA Classification Criteria were invited to participate in the study after the subjects gave their written informed consent. Peripheral blood samples and clinical records were obtained from 21 RA patients (19 females and 2 males) and 5 healthy volunteers (5 females) served as control. The expression of CD14, CD16, CD16b, CD3 and CD203c on blood cells was measured by flow cytometric analysis. Disease activity of RA was evaluated by the 28-joint Disease Activity Score-ESR. The statistical significance of difference between two groups was determines by Wilcoxon signed rank test. Results: CD16b+CD14+ monocytes were significantly increased in RA patients (2.58±1.58%) compared with healthy controls (0.60±0.43%) (p=0.0018), whereas CD16+CD14+ monocytes were not significantly increased in RA patients (p=0.15). Moreover, the percentage of CD16b on CD14+ monocytes was significantly high in RA patients with high or moderate disease activity compared with those with low disease activity (p=0.0049). On the other hand, the percentage of CD16b on CD14-CD3- cells and CD203c+ cells were comparable between RA patients and healthy controls. Conclusions: Fc gamma receptor 3b (CD16b) was aberrantly expressed on CD14+ monocytes in patients with RA, whereas the expression of CD16b in other cell subsets was comparable between RA patients and healthy individuals. The result might provide additional information of infusion reaction to biological agents and IgG-mediated immunological reaction in RA. References: Ann Rheum Dis 70:299, 2011 ACR #2160, 2012 Disclosure of Interest: M. Tsukamoto: None Declared, K. Yoshimoto: None Declared, H. Kameda: None Declared, T. Takeuchi Grant/research support from: Abbott Japan Co., Ltd., Astellas Pharma, Bristol-Myers K.K., Chugai Pharmaceutical Co., Ltd, Daiichi Sankyo Co., Ltd., Eisai Co., Ltd., Janssen Pharmaceutical K.K., Mitsubishi Tanabe Pharma Co., Nippon Shinyaku Co., Ltd., Otsuka Pharmaceutical, Pfizer Japan Inc., Sanofi-aventis K.K., Santen Pharmaceutical Co., Ltd., Takeda Pharmaceutical Co., Ltd., Teijin Pharma Ltd., Consultant for: Abbott Japan Co., Ltd., Bristol-Myers K.K., Chugai Pharmaceutical Co., Ltd., Eisai Co., Ltd., Janssen Pharmaceutical K.K., Mitsubishi Tanabe Pharma Co., Pfizer Japan Inc., Takeda Pharmaceutical Co., Ltd., Astra Zeneca, K.K., Eli-Lilly Japan K.K., Novartis Pharma K.K., Asahi Kasei Medical K.K.